North, Iran-Contra, and the Doomsday Project: The Original Congressional Cover Up of Continuity-of-Government Planning - Peter Dale Scott (Japan Focus)
In 1989 I published the following article, "Northwards without North: Bush, Counterterrorism, and the Continuation of Secret Power." It is of interest today because of its description of how the Congressional Iran-Contra Committees, in their investigation of Iran-Contra, assembled documentation on what we now know as Continuity of Government (COG) planning, only to suppress or misrepresent this important information in their Report. I was concerned about the committees' decision to sidestep the larger issues of secret powers and secret wars, little knowing that these secret COG powers, or "Doomsday Project," would in fact be secretly implemented on September 11, 2011. (One of the two Committee Chairs was Lee Hamilton, later co-chair of the similarly evasive 9/11 Commission Report).Recently I have written about the extraordinary power of the COG network Doomsday planners, or what CNN in 1991 described as a "shadow government...about which you know nothing." Returning to my 1989 essay, I see the essential but complex overlap between this Doomsday Committee and the Iran-Contra secret "junta" or cabal described by Theodore Draper and Senator Paul Sarbanes within the Reagan-Bush administration. This article explores those connections and their implications for American democracy and American power in the Middle East.